PENGARUH PEMBELAJARAN ONLINE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS VIII SMP NEGERI 52 SATAP HALMAHERA SELATAN - Narilah A Tuara; Nurlaila H Tasanif (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
Online learning is a form of learning that utilizes digital devices and internet networks to support the teaching and learning process. The implementation of online learning is expected to improve student motivation and learning outcomes through optimal use of technology. This study aims to analyze the effect of online learning on learning motivation and learning outcomes of eighth-grade students of SMP Negeri 52 SATAP South Halmahera in Economics. This study uses a quantitative approach with an associative research type and ex-post facto design. The research sample consisted of 46 students selected using random sampling techniques from a total population of 86 students. Data were collected through questionnaires and documentation, then analyzed using descriptive analysis and correlation to test the relationship between variables. The results showed that online learning was in the very good category (81.1%), learning motivation was in the very good category (82.3%), while learning outcomes were in the good category (77.6%). The analysis of the relationship between variables showed that online learning had an effect on learning motivation with a coefficient of 38.7% and on learning outcomes by 40.6%. These findings indicate that online learning makes a positive contribution to increasing student motivation and learning outcomes, although the extent of the influence is still influenced by other factors outside the model studied.